1987
DOI: 10.1123/tsp.1.4.309
|View full text |Cite
|
Sign up to set email alerts
|

The Sport Psychology Consultant Evaluation Form

Abstract: An evaluation inventory was developed to help sport psychology consultants assess and improve the field services they provide. Consultant characteristics included in the inventory were based on extensive interviews with Olympic athletes and coaches. The inventory was administered to 104 Canadian Olympic athletes who assessed 26 sport psychology consultants. Data from this survey were used to determine the validity and reliability of the Sport Psychology Consultant Evaluation Form (CEF). Practical suggestions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…The knowledge, delivery style, and characteristics of the individual sport psychologist have a central influence on the overall effectiveness of the service (Partington & Orlick, 1987). Petitpas, Giges, and Danish (1999) suggested that the practitioner's skills in developing a working relationship characterized by trust, openness, and collaboration with the athlete are important in determining the effectiveness of the support.…”
Section: Quality Of Supportmentioning
confidence: 99%
See 3 more Smart Citations
“…The knowledge, delivery style, and characteristics of the individual sport psychologist have a central influence on the overall effectiveness of the service (Partington & Orlick, 1987). Petitpas, Giges, and Danish (1999) suggested that the practitioner's skills in developing a working relationship characterized by trust, openness, and collaboration with the athlete are important in determining the effectiveness of the support.…”
Section: Quality Of Supportmentioning
confidence: 99%
“…That is, as professionals, sport psychologists should continually strive to improve their effectiveness and provide the best possible service they can. Partington and Orlick (1987) noted that by subjecting themselves to evaluation, sport psychologists give a clear indication that they are "committed to pursuing personal excellence in (their) consultation field in the same way that athletes are committed to pursuing excellence in their field of sport" (p. 316). Pertinent evaluative feedback will enable practitioners to develop their own skills and learn how to improve their effectiveness (Milne, 1987;Weigand, Richardson, & Weinberg, 1999).…”
Section: Consideration 2: Why Evaluate Aspp?mentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation was carried out using (1) a comparison of the number and level of UEFA/FIFA refereeing appointments that were awarded in the seasons before, during and after the intervention period (2) an analysis of an interview that explored the referee"s perceptions of the intervention programme and (3) the Sport Psychology Consultant Evaluation Form (SPCEF) (Partington & Orlick, 1987). The qualitative data was collected during a semi structured interview that was carried out by an independent researcher who was not involved in any aspect of the intervention delivery.…”
Section: Discussionmentioning
confidence: 99%